Factors Influencing The Inflation of Indonesia In Islamic Perspectives - Anton Bawono (Jurnal Ilmiah Ekonomi Islam, 2019)
The purpose of the study is to identify the factors that influence inflation, using secondary data from 1987 to 2017. Methods for analyzing data using multiple linear regression. The result of the study shows that money supply has a positive and significant effect on inflation while economic growth has a negative and significant effect on inflation occurs in Indonesia. While interest rates do not have an influence on inflation occurs in Indonesia.